PERSEPSI PETANI DAN EFEKTIVITAS KELOMPOK TANI DALAM PROGRAM UPSUS PAJALE DI KECAMATAN BANJAR BARU KABUPATEN TULANG BAWANG - Riandari Irsa; Dewangga Nikmatullah; Kordiyana K Rangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The purposes of this research are to analyze farmer’s perception in Upsus Pajale Program, to find out the factors related with farmer’s perception in Upsus Pajale Program, effectiveness of farmer groups on Upsus Pajale Program, and the relationship between the perception and the effectiveness in implementation of Upsus Pajale Program in Banjar Baru.  This research was conducted in Banjar Baru subdistrict, Tulang Bawang district with 67 respondents of rice farmers following the Program. Data were collected using a suvey method with descriptive analysis and use nonparametric statistics test rank Spearman correlation to examine the hypotesis.  The results showed that farmer’s perception in Upsus Pajale Program is included in the profitable calssification, the factors related are education, motivation, social environment and the support of government agencies, while the unrelated factor is knowledge level. The effectiveness of farmer group is in effective category and farmer’s perception is related with farmer group effectiveness.Key words: farmer group effectiveness, farmer’s perceptions, Upsus Pajale Program